Incorporating Indigenous Content to Develop English Materials for Primary School Levels: The Teachers' Voices - Nuraeningsih; Rusiana; Titis Sulistyowati; Richma Hidayati (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2025)
The present research explores primary school teachers’ perceptions of the possibility of integrating indigenous content in English instruction in Indonesia. The current curriculum, Kurikulum Merdeka, allows teachers to develop materials related to essential content. With that image in mind, this research tried to shed light on the opportunities and challenges of incorporating indigenous content, such as local folktales, songs, games, and traditions, to develop English materials. The research employs a qualitative research method. The participants were five teachers from different subdistricts in Kudus, Central Java, Indonesia. They were purposively selected and voluntarily participated in the research. A focus group discussion was carried out to gain the teachers’ insights. The questions address three main points: the objectives of English teaching in primary schools, the incorporation of indigenous content into English materials, and the challenges faced when integrating this content into those materials. The triangulation was conducted by collecting the teachers’ written responses on the same topic with more detailed questions. Thematic analysis was used to analyse the data. The research findings reveal that teachers have a positive view of the inclusion of indigenous content in English instruction, as it is relevant to students’ real-life contexts. The challenges that might emerge are limited resources, insufficient training, and lack of experts and authority. support. Practically, teachers can introduce indigenous content into the teaching materials. In wider contexts, curriculum designers are recommended to consider addressing indigenous content in the English curriculum for primary school students.